2005
DOI: 10.1007/s10725-005-1046-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ATP on cucumber (Cucumis sativus L.) regeneration from nodal explants: association with α-tocopherol, H2O2 and size of culture vessel

Abstract: We investigated the effect of adenosine 5¢-triphosphate (ATP), a-tocopherol and H 2 0 2 on the micropropagation of cucumber (Cucumis sativus L.) from nodal explants. The effect of the size of the liquid culture vessel (250-ml flask vs. 2.5-l airlift bioreactor) was also evaluated. The addition of ATP alone caused a significant increase in the number of branches (internodes) and in internodal length, but also a reduction of leaf number, compared to control cultures. It also increased significantly the accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(22 reference statements)
1
2
0
Order By: Relevance
“…Finally, the improving effects of antioxidants on growth characters might be attributed to their positive action on enhancing cell divisions and protecting plant cells from free radicals that responsible for plant sencences (Raskin, 1992).The positive effect of α-tocopherol on plant growth is in harmony with many findings on earlier results from literature on some plant species i.e. Tanczos et al (1982)on rice, Matakiadis and Kintzios (2005) on cucumber plants.…”
Section: -Vegetative Growthsupporting
confidence: 76%
“…Finally, the improving effects of antioxidants on growth characters might be attributed to their positive action on enhancing cell divisions and protecting plant cells from free radicals that responsible for plant sencences (Raskin, 1992).The positive effect of α-tocopherol on plant growth is in harmony with many findings on earlier results from literature on some plant species i.e. Tanczos et al (1982)on rice, Matakiadis and Kintzios (2005) on cucumber plants.…”
Section: -Vegetative Growthsupporting
confidence: 76%
“…ATP, alone or in combination with antioxidants, is a growth regulator for the micropropagation of cucumber from nodal explants and has commercial potential (Matakiadis & Kintzios 2005). ATP is released by plant cells and acts to suppress a default death pathway, and some forms of pathogen‐induced cell death are mediated by the depletion of extracellular ATP (Chivasa et al.…”
Section: Plantsmentioning
confidence: 99%
“…Some authors noted that addition of either ATP or ADP caused a significant increase in cell division of in vitro synchronized potato (Ipomea batatas L.), cucumber (Cucumis sativus L.) and duckweed (Spirodella polyrhiza L.) cell suspension cultures (Kintzios et al 2002). Others mentioned that addition of ATP had positive effect on cucumber (Cucumis sativus L.) regeneration from nodal explants (Matakiadis and Kintzios 2005). The authors observed significant increasing number of internodes and length, but also noted a reduction of leaf number as effect of ATP addition.…”
Section: Introductionmentioning
confidence: 96%